Migration and development in the West Indies - Reubens, Edwin Pierce ([Mona] Jamaica, Institute of Social and Economic Research, University College of the West Indies)
This is an economic and social study of migration as a differential flow among the territories of the West Indies Federation.
Bibliographical footnotes.
gp. 21/01/2019
loan
Keywords: Migration, Internal; Labor supply; West Indies, British